R&D Expenditures and Their Impact on Innovation in the Digital Era: A Kazakhstan Perspective - G. G. Seitkan; P. Karacsony; N. K. Zaitenova; A. Konysbay (Экономика: стратегия и практика)
The article aims to assess the relationship between research and development costs and the level of innovation activity of enterprises in Kazakhstan. The research methodology involves correlation analysis, applying quantitative methods to analyze the collected data from official statistical yearbooks from 2007 to 2022. Correlation analysis with five variables on innovation activity and the impact of research and development costs on that, using Excel and Smart PLS 4 programs were used. According to the results of research, there was a positive impact of R&D expenditure on the level of innovation activity of enterprises mostly, secondly on the ratio of innovative product to gross domestic product, volume of innovative products (goods, services), and showing not so strong correlation on costs of product and process innovations. Digital hubs perform as an ecosystem with a network approach, including organizations in a region to undergo digital transformation in the era of the digital economy and digital technologies. The results of current research might be helpful to academicians and public administration. The originality of the study consists in assessing the impact of R&D expenditure on innovation management in a particular level of innovation activity, the share of innovative products about GDP, costs of product and process innovations, the volume of innovative products (goods, services) to a proper subsequent further contribution. As a result, it is recommended that policy measures focus on enhancing digital infrastructure and supporting R&D investments to ensure sustained innovation performance and economic development.